2018
DOI: 10.1109/jiot.2017.2705560
|View full text |Cite
|
Sign up to set email alerts
|

IoT-Driven Automated Object Detection Algorithm for Urban Surveillance Systems in Smart Cities

Abstract: Automated object detection algorithm is an important research challenge in intelligent urban surveillance systems for IoT and smart cities applications. In particular, smart vehicle license plate recognition (VLPR) and vehicle detection are recognized as core research issues of these IoT-driven intelligent urban surveillance systems. They are key techniques in most of the traffic related IoT applications, such as road traffic real-time monitoring, security control of restricted areas, automatic parking access … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(54 citation statements)
references
References 17 publications
0
52
0
2
Order By: Relevance
“…Another advantage of our method is that it does not depend on object motion; even nonmoving objects are detected automatically. In [11], we proposed a simple filter for detecting vehicles or license plates from captured images. We found that an object (for example, a vehicle or human being) is normally the highest energy frequency aspect of an image and the energy frequency curves decrease sharply outside object boundaries.…”
Section: Our Proposed Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another advantage of our method is that it does not depend on object motion; even nonmoving objects are detected automatically. In [11], we proposed a simple filter for detecting vehicles or license plates from captured images. We found that an object (for example, a vehicle or human being) is normally the highest energy frequency aspect of an image and the energy frequency curves decrease sharply outside object boundaries.…”
Section: Our Proposed Methodsmentioning
confidence: 99%
“…To do so, the computer determines whether or not this image can be used as a background. Using the pretreatment method proposed in [11], we first transfer the original image into a gray-scale image to reduce the image data that must be calculated. After generating the grayscale image, we calculate its gradient using P x to denote differences in the x direction (horizontal) and P y to denote differences in the y direction (vertical).…”
Section: Pre-treatment Of the Captured Imagementioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in the work of Lu et al, traffic conditions of an urban area are monitored in real time by exploiting the capabilities of smart cameras that are able to preprocess and filter information before sending them to a remote server. Furthermore, the work of Hu and Ni introduced an algorithm for license plate recognition through smart cameras on the basis of a lightweight filter for digital camera sensors to reduce network bandwidth and latency. As far as large metropolitan areas are concerned, data and information fusion techniques on the server/cloud side can be used to properly investigate underlying physical phenomena and events captured by an ISS as discussed in the work of Fan et al Indeed, enhanced elaboration can be performed by exploiting big data techniques as shown in the work of Shao et al, where a novel workflow exploiting (big) surveillance data based on event detection and alarming messages from front‐end smart cameras is proposed.…”
Section: Overview Of the Problem And Related Workmentioning
confidence: 99%